Motivations for Capital Controls and Their Effectiveness - Radhika Pandey; Gurnain K. Pasricha; Ila Patnaik; Ajay Shah (Bank of Canada, 2015)
We assess the motivations for changing capital controls and their effectiveness in India, a country with extensive and long-standing controls. We focus on the controls on foreign borrowing that can, in principle, be motivated by macroprudential concerns. We construct a fine-grained data set on capital control actions on foreign borrowing in India. Using event study methodology, we assess the factors that influence these capital control actions, the main factor being the exchange rate. Capital controls are tightened after appreciation, and eased after depreciation, of the exchange rate. Macroprudential concerns, measured by variables that capture systemic risk buildups, do not seem to be a factor shaping the use of capital controls. To assess the impact of controls, we use both event study and propensity score matching methodologies. Event study methodology suggests no impact of capital controls on most variables evaluated, but reveals limited evidence that capital controls relieve currency pressures in the short term. However, even this limited evidence disappears once selection bias is controlled for.
Keywords: F32; G15; G18; 330; International topics; Financial stability; Exchange rate regimes; Financial system regulation and policies